2018
DOI: 10.1134/s1607672918020047
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Expression of Adhesion Molecule and Extracellular Matrix Genes in Mesenchymal Stromal Cells after Interaction with Cord Blood Hematopoietic Progenitors

Abstract: The dynamics of the expression of genes encoding adhesion molecules, molecules of the connective tissue matrix, and its remodeling enzymes was studied in multipotent mesenchymal stromal cells (MSCs) from human adipose tissue after interaction with cord blood hematopoietic progenitors (HSPCs). An upregulation of ICAM1 and VCAM1, directly proportional to the coculture time (24-72 h), was found. After 72 h of culturing, a downregulation of the genes encoding the majority of matrix molecules (SPP1; COL6A2,7A1; MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…HSPCs) for their viability and proliferation, through direct/ paracrine cell-to-cell interactions [34,35]. In addition, ASCs can also upregulate the adhesion molecule and extracellular matrix genes in HSPCs, which was good for the latter to anchor and survive in the local area [36].All aforementioned evidence demonstrated that the paracrine factors that secreted by ASCs might be used by CBMNCs for survival and function when they are co-transplanted simultaneously. So, we need to nd new strategies to improve the treatment e cacy.…”
Section: Discussionmentioning
confidence: 97%
“…HSPCs) for their viability and proliferation, through direct/ paracrine cell-to-cell interactions [34,35]. In addition, ASCs can also upregulate the adhesion molecule and extracellular matrix genes in HSPCs, which was good for the latter to anchor and survive in the local area [36].All aforementioned evidence demonstrated that the paracrine factors that secreted by ASCs might be used by CBMNCs for survival and function when they are co-transplanted simultaneously. So, we need to nd new strategies to improve the treatment e cacy.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, heterogeneous effects of MSC on GSIS may partly result from different expression levels of ANXA1. Likely, the very close proximity of MSC and islets in direct co-cultures enhanced local effector levels and involves the extracellular matrix (ECM) since MSC cocultured with HSC maintain the vascular niche by upregulated expression of intercellular adhesion molecule 1 (ICAM1) and vascular cell adhesion molecule 1 (VCAM1) [149]. Such supportive processes are an important topic in tissue engineering and it has been recognized that islets, which lost ECM during enzymatic isolation, show improved survival and function after treatment with ECM molecules [150].…”
Section: Humoral Potential Of Mscmentioning
confidence: 99%
“…Studies investigating the mutual interactions between stem cell subpopulations are also in their infancy. It has been shown that CB hematopoietic progenitors influence the expression of genes encoding for adhesion molecules and molecules of the connective tissue matrix [143]. Its remodeling enzymes was also studied in multipotent mesenchymal stromal cells (MSCs) from human adipose tissue [144].…”
Section: Past and Future Perspectivesmentioning
confidence: 99%